The effect of gender on equity ownership: focusing on the mediating roles of financial literacy - Hall, Gina Lynn (Kansas State University, 2023)
This dissertation research explored the potentially mediating variable of financial literacy on the relationship between gender and equity ownership. Females typically live longer than males; therefore, they need to be willing and able to take more investment risk by owning equities to account for the additional income required to reach a possible extended age. This study examined three financial literacy factors (financial knowledge, financial ability, and financial confidence) to determine why previous research has found the opposite to be true (Brooks et al., 2019; Charness & Gneezy, 2012; Gudmunson & Danes, 2011; Marinelli et al., 2017; Montford & Goldsmith, 2016). The theoretical framework and definition for financial literacy, as described by Huston (2010) was utilized throughout the study and two comparison datasets were reviewed including the 2021 National Financial Capability Study (NFCS) as well as the 2019 Survey of Consumer Finances (SCF). According to Huston (2010), there are two distinct components of financial literacy, which are separated into the “knowledge dimension” and the “application dimension” (p. 307). Huston (2010) postulated that all three factors affect financial behavior and well-being, when accounting for outside influences such as family/peer financial socialization, self-control problems, socioeconomic/community conditions, and time preferences. Based on this theory, cognitive limitations in financial knowledge (found within Huston’s “knowledge dimension”) as well as financial ability and confidence (found within Huston’s “application dimension”) (p. 307), would influence a person’s financial outcomes and were reviewed throughout the study. The 2021 NFCS sample was reduced to the 2,824 respondents that have investments outside of their retirement accounts to pinpoint particular and intentional investment decisions. This sample subset is known as the “Investors Survey” within the NFCS. These investors were asked several clarifying questions regarding their investment holdings outside of their retirement assets. The 2019 SCF consisted of 5,777 respondent households and multiple imputation techniques were utilized to account for missing data and to ensure respondent privacy, for a total of 28,885 observations. The research focused on equity ownership, gender, and financial literacy; therefore, the sample was reduced to 20,183 respondent observations that had brokerage accounts, public stock accounts and/or managed investment accounts outside of their retirement assets to pinpoint particular and intentional investment decisions. Understanding the relationship between gender and equity ownership is increasingly important for the financial planning profession given expanded life expectancies for females. Overall, results from both datasets indicated that there were direct negative relationships between gender and financial literacy, direct positive relationships between financial literacy and equity ownership, both the NFCS and SCF datasets showed significant direct and indirect (mediating) relationships between gender and equity ownership when factoring in the above-mentioned financial literacy variables.
Keywords: Financial literacy; Gender; Equity ownership; Financial knowledge; Financial confidence; Financial ability